Novel circGFRα1 Promotes Self-Renewal of Female Germline Stem Cells Mediated by m6A Writer METTL14 - Li, Xiaoyong; Tian, Geng; Wu, Ji (Frontiers in Cell and Developmental Biology, 2021)
Circular RNAs (circRNAs) play important roles in the self-renewal of stem cells. However, their significance and regulatory mechanisms in female germline stem cells (FGSCs) are largely unknown. Here, we identified an N6-methyladenosine (m6A)-modified circRNA, circGFRα1, that is highly abundant in mouse ovary and stage-specifically expressed in mouse FGSC development. Knockdown of circGFRα1 in FGSCs significantly reduced their self-renewal. In contrast, overexpression of circGFRα1 enhanced FGSC self-renewal. Mechanistically, circGFRα1 promotes FGSC self-renewal by acting as a competing endogenous RNA (ceRNA) that sponges miR-449, leading to enhanced GFRα1 expression and activation of the GDNF signaling pathway. Furthermore, circGFRα1 acts as a ceRNA based on METTL14-mediated cytoplasmic export through the GGACU motif. Our study should help to understand the mechanisms regulating germ cell development, add new evidence on the mechanism of action of circRNA, and deepen our understanding of the development of FGSCs.